Zinc as a Biomarker of Cardiovascular Health - Knez, Marija; Glibetic, Maria (Frontiers in Nutrition, 2021)
The health importance of Zn continues to expand recognition. Compromised Zn homeostasis and prolonged inflammation are common features in various CVDs. Zn deficiency has a role in the development of CVDs and Zn status can be a determining factor in cardiovascular health. Zn biochemistry is implicated in vascular processes. Zn supplementation is beneficial for the management of cardio-metabolic diseases and Zn manipulations could be employed in the prevention and treatment of CV disorders. Long-term well-designed studies performed in various population groups should be pursued to additionally clarify significant relationships between Zn and CVDs.